Caracterização bioquímica e funcional de isolados proteicos e genótipos de excelência de feijão-caupi [Vigna unguiculata (L.) Walp.] - Medeiros, Jackeline Lima de (2013)
The cowpea (Vigna unguiculata (L.) Walp) is an important plant due to their nutritional potential, revealed to mainly high protein content. The highlight proteins present in the functional properties (technological) and interest in new sources of protein at affordable costs leads to increasing interest in studying the legume. Thus, the present study aimed to obtain protein isolates from bean cowpea genotypes, as the biochemical and functional characterization of these isolates and their seeds. The results showed the seeds are good sources of protein (23.19 to 24.02%), fiber (17.75 to 19.78%) and have a low lipid content (1.67%). The protein isolated obtained showed high purity (above 90%) and yield (35.11 and 38.12%). Both isolated as seeds not proved toxic but exhibited trypsin inhibitor (24.2 to 28.2 IU), chymotrypsin (26.66 to 32.17 IU) and lectin (80.000-320.000 IU). The digestibility of isolated (63.23 and 63.81%) was higher than the seeds (50.07 to 54.37%). The predominant proteic fraction was globulin, with the highest concentration in the isolates. The seeds and isolated solubilities presents U-shaped, with lower solubility at the isoelectric point. The isolated protein showed greater capacity for absorb water (2.41 to 2.44 ml/g sample), oil (from 2.38 to 2.81 ml / g sample) and gel concentrations (8-10%). Already seeds showed higher foaming (52.66 to 57.89%).